Emergency Landing Spot Detection for Unmanned Aerial Vehicle - Loureiro, Gabriel da Silva Martins (2021)
The use and research of Unmanned Aerial Vehicle (UAV) have been increasing over the years due to the applicability in several operations such as search and rescue, delivery, surveillance and others. Considering the increased presence of these vehicles in the airspace, it becomes necessary to reflect on the safety issues or failures that UAV may have and what is the appropriate action to take. Furthermore, in many missions the vehicle will not return to its original location and, in case of fail to achieve the landing spot, need to have onboard capability to estimate the best spot to safely land. The vehicles are susceptible to external disturbance or electromechanical malfunction. In this emergency’s scenarios, UAVs must safely land in a way that will minimize damage to the robot and will not cause any human injury. The suitability of a landing site depends on two main factors: the distance of the aircraft to the landing site and the ground conditions. The ground conditions are all the factors that are relevant when the aircraft is in contact with the ground, such as slope, roughness and presence of obstacles. This dissertation addresses the scenario of finding a safe landing spot during operation. Therefore, the algorithm must be able to classify the incoming data and store the location of suitable areas. Specifically, by processing Light Detection and Ranging (LiDAR) data to identify potential landing zones and evaluating the detected spots continuously given certain conditions. In this dissertation, it was developed a method that analyses geometric features on point cloud data and detects potential good spots. The algorithm uses the Principal Component Analysis (PCA) to find planes in point clouds clusters. The planes that have slope less than a threshold are considered potential landing spots. These spots are then evaluated regarding ground and vehicles conditions such as the distance to the UAV, presence of obstacles, roughness of the area, slope of the spot. The output of the algorithm is the optimum spot to land and can vary during operation.